Generation and Acceleration of Isolated- Attosecond Electron Bunch via Phase-Compressed Injection - Liang-Qi Zhang; Mei-Yu Si; Tong-Pu Yu; Yuan-Jie Bi; Yong-Sheng Huang (Ultrafast Science)
We propose a novel scheme for generating and accelerating simultaneously a dozen-GeV isolated attosecond electron bunch via phase-compressed injection in a radiative–wakefield–breaking process from an electron beam-driven hollow-channel plasma target. During the beam–target interaction, transverse oscillations of plasma electrons are induced, and subsequently, a radiative wakefield is generated. Meanwhile, a large number of plasma electrons of close to the speed of light are injected transversely toward the center of the hollow channel from the position of the transverse electric field of radiative wakefield, forming an isolated attosecond electron bunch due to the phase compression in the radiative–wakefield–breaking process. The injected attosecond electron bunch is then located just in the acceleration phase of the longitudinal electric field of the radiative wakefield and is importantly accelerated to high energies by the radiative wakefield. It is demonstrated theoretically and numerically that this scheme can efficiently generate an isolated attosecond electron bunch with a charge of more than 2 nC, a peak energy up to 13 GeV of more than 2 times that of the driving electron beam, a peak divergence angle of less than 5 mrad, a duration of 276 as, and an energy conversion efficiency of 36.7% as well as a high stability as compared with the laser-beam drive case. Such an isolated attosecond electron bunch in the range of GeV would provide critical applications in ultrafast physics and high-energy physics.